Waging peace in Mindanao : the Aquino way - Ava Patricia C. Avila (2012)
The resumption of the peace talks marks the first attempt of President Benigno C. Aquino III to end the separatist conflict in Mindanao despite factional divides that threaten the negotiation process. A key aspect is the shift to a human security approach articulated in the new internal security plan.